Conversion of Cellulosic Waste into Fermentable Sugar: Process Optimization - Khan, Maksudur R.; Salam, M. A.; Pondith, Paritush Chandra; Islam, Ariful; Uddin, Mohammad Rakib; M. A., Islam (JOL, 2013)
Fossil fuel is depleting day by day throughout the world. This limitation along with the problem of Green House Gas (GHG) emissions leads findings for alternative energy that are environmentally and commercially feasible. Every day we are dumping lot of cellulosic waste materials into the environment from which we can produce valuable product such as ethanol to trim down the energy demand on fossil fuel. In the present study waste paper was treated to produce fermentable sugar using both conventional and enzymatic process. Acid catalyzed hydrolysis is conducted using sulfuric acid and the enzymatic process utilized municipal drain sludge. For acid catalyzed process optimum glucose concentration was found around 4 mg/ml for a loading of 1.5 g of untreated waste paper in 100 ml working volume at 25±2°C and a PH of 5 in about 1.5 hrs of hydrolysis. In case of enzymatic hydrolysis glucose yield was found around 2.5 mg/L for 10 ml sludge dosing in 100 ml working volume at 30°C±2 and PH of 7 in about 1.15 hrs of operation. In addition, base catalyzed hydrolysis is also observed with 5% NaOH and results around 3.3 mg/ml of glucose at room temperature and a PH of 13.0 in 1.5 hrs of hydrolysis